2013
DOI: 10.4274/tjo.43.27880
|View full text |Cite
|
Sign up to set email alerts
|

Pterjium Oluşmasında Mesleğin Etkileri

Abstract: ÖzetAmaç: Pterjium oluşmasında mesleğin etkilerini araştırmak. Ge reç ve Yön tem: Kahramanmaraş Pazarcık Devlet Hastanesi Göz Hastalıkları Polikliniğinde Ağustos 2012-Ekim 2012 tarihleri arasında muayene olup pterjium tanısı alan 182 hastanın dosyası geriye dönük olarak incelendi. Hastaların meslekleri analiz edildi ve mesleklerin pterjium oluşumundaki etkileri araştırıldı. Sonuçlar: Çalışmamıza muayene edilen 2328 hastadan, pterjium tanısı alan 182 (%7,8) hasta dâhil edilmiştir. Olguların ortalama yaşı 52,2±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition to this factor, advanced age, male gender, low education level, high systolic blood pressure, living in rural areas and dry eye have also been associated with increased pterygium incidence. 3,8,9,10 In the current study, 75% of the patients were male, the nature of their occupations indicated low education level.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In addition to this factor, advanced age, male gender, low education level, high systolic blood pressure, living in rural areas and dry eye have also been associated with increased pterygium incidence. 3,8,9,10 In the current study, 75% of the patients were male, the nature of their occupations indicated low education level.…”
Section: Discussionmentioning
confidence: 45%
“…Previous studies have also shown higher incidence and increased severity of pterygium in agricultural workers and farmers. 10 Threlfall and English4 demonstrated a strong association between sun exposure and pterygium. They concluded that sun exposure should be avoided as much as possible and emphasized that all ages should use hats or sunglasses for eye protection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation